Superalloy 718 and Derivatives 2010
DOI: 10.1002/9781118495223.ch57
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of δ Phase Microstructure in Alloy 718

Abstract: Though Alloy 718 is strengthened by γ″ precipitation, the nucleation of δ phase is used to stabilize grain size and also to improve its high temperature stress rupture properties. Large body of work has been reported in the literature on the precipitation of the γ″ phase. However, hardly very few reports are available on the evolution of δ particles in Alloy 718. The present paper reports the results of a detailed microstructural investigation carried out using Transmission Electron Microscopy (TEM) and Scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…The USAXS dimensionalities of the δ phase precipitates are also in good agreement with the values identified from the SEM results (after 8 h, diameter at (815 ± 157) nm and thickness at (48 ± 6) nm). Previous TEM micrographs of δ phase in AM IN625 heat-treated at 870 °C for 1 h demonstrated that the precipitates are highly crystalline and that the orientation relationship between the FCC matrix and δ phase precipitates follows {111} FCC //(100) δ and <11̄0> FCC //[100] δ , a result also identified in an earlier TEM study of δ phase in 718 alloy [23,82]. In particular, it was reported that in each close-packed plane, three variants of δ phase can form with their long axes aligned with the close-packed directions in the FCC matrix.…”
Section: Resultssupporting
confidence: 62%
“…The USAXS dimensionalities of the δ phase precipitates are also in good agreement with the values identified from the SEM results (after 8 h, diameter at (815 ± 157) nm and thickness at (48 ± 6) nm). Previous TEM micrographs of δ phase in AM IN625 heat-treated at 870 °C for 1 h demonstrated that the precipitates are highly crystalline and that the orientation relationship between the FCC matrix and δ phase precipitates follows {111} FCC //(100) δ and <11̄0> FCC //[100] δ , a result also identified in an earlier TEM study of δ phase in 718 alloy [23,82]. In particular, it was reported that in each close-packed plane, three variants of δ phase can form with their long axes aligned with the close-packed directions in the FCC matrix.…”
Section: Resultssupporting
confidence: 62%
“…In addition, the intergranular δ-phase was brighter than the intragranular ones due to its larger content of Nb. Presumably, the δ-phase started its precipitation at the grain boundaries; however, as the temperature or dwell time increased (lower cooling rate~300 K/s), the intragranular δ-phase precipitates can appear [29], as shown in Fig. 5b.…”
Section: Microstructures Of the Ebm Samples In All Groupsmentioning
confidence: 99%
“…It is shown in Figure 12 (A_COS, B_COS and C_COS) that a few needle-like phases are precipitated in the interdendritic regions, including the Laves phase. The needle-like phases are identified as a δ-phase [21] and it is also observed by the XRD analysis. The presence of this δ-phase is more in the A_COS samples than in B_COS and C_COS samples.…”
Section: Apparition Of Laves Phase and Hot Cracking Formationmentioning
confidence: 78%